Is dynamic rotation training able to improve futsal athlete performance? - Sugeng Purwanto; Moch Fath Khurrohman (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
The performance of an athlete is determined by their game skill and technique, which become important components to achieving the game's objectives. Empirically, this study aimed to test the effect of providing dynamic rotation training on futsal athlete playing performance. This experimental study involved 20 futsal athletes aged 16-19 years in Banyumas Regency (Age= M 17,6 ± BMI 20,3 kg/m2). Futsal special performance test was used to measure the futsal player playing performance. The analysis involved skill components (passing, controlling, dribbling, and shooting) and physical aspects (speed and agility). Furthermore, results showed that providing dynamic rotation training could significantly increase the performance of futsal athletes aged 16-19 years (p-value = 0,001). These findings become the foundation that a coach needs to be concerned with to select an effective exercise to impact the athletes positively.